The skeletal muscle circadian clock regulates titin splicing through RBM20 - Riley, Lance A.; Zhang, Xiping; Douglas, Collin M; Mijares, Joseph M; Hammers, David W; Wolff, Christopher A; Wood, Neil B; Olafson, Hailey R; Du, Ping; Labeit, Siegfried; Previs, Michael J; Wang, Eric T; et al. (eLife, 2022)
Circadian rhythms are maintained by a cell-autonomous, transcriptional-translational feedback loop known as the molecular clock. While previous research suggests a role of the molecular clock in regulating skeletal muscle structure and function, no mechanisms have connected the molecular clock to sarcomere filaments. Utilizing inducible, skeletal muscle specific, Bmal1 knockout (iMSBmal1-/-) mice, we showed that knocking out skeletal muscle clock function alters titin isoform expression using RNAseq, liquid chromatography-mass spectrometry, and sodium dodecyl sulfate-vertical agarose gel electrophoresis. This alteration in titin’s spring length resulted in sarcomere length heterogeneity. We demonstrate the direct link between altered titin splicing and sarcomere length in vitro using U7 snRNPs that truncate the region of titin altered in iMSBmal1-/- muscle. We identified a mechanism whereby the skeletal muscle clock regulates titin isoform expression through transcriptional regulation of Rbm20, a potent splicing regulator of titin. Lastly, we used an environmental model of circadian rhythm disruption and identified significant downregulation of Rbm20 expression. Our findings demonstrate the importance of the skeletal muscle circadian clock in maintaining titin isoform through regulation of RBM20 expression. Because circadian rhythm disruption is a feature of many chronic diseases, our results highlight a novel pathway that could be targeted to maintain skeletal muscle structure and function in a range of pathologies.
Gesehen am 02.10.2023